Two new occurence species of the genus Cenchrus L. (Poaceae Barnh.) for the flora of Vietnam - Phuong Anh, Tran Thi (Academia Journal of Biology, 2012)
The genus Cenchrus L. had about 25 species, distributed commonly throughout the world. In Vietnam this genus had recorded by G. Camus et A. Camus, 1912-1923 with 1 species (Cenchrus inflexus), Pham Hoang Ho (1993), Nguyen Thi Do et Nguyen Khac Khoi (2005) with 2 species, according these, C. inflexus as synonym of C. brownii and 1 cultivated species C. ciliaris. In this article, we had described Cenchrus echinatus L. and C. setigerus Vahl as a new record for the flora of Vietnam. C. echinatus differed from C. ciliaris and C. brownii by inner involucral bristles connate in to cup, retrorsely scaberulous, outer involucral bristles shorter than inner; C. setigerus differed from the others by inner involucral bristles connate into cup, antrorsely scaberulous, grooved on outer face, outer involucral bristles few, shorter than inner  These species was collected in the Quang Ninh, Ninh Thuan and Thua Thien - Hue provinces.